Practicas inclusivas de socialización a través del juego, para niños de educación inicial, en la escuela “Luis Felipe Borja” en la provincia de Pichincha, cantón Mejía, ciudad Machachi durante el periodo lectivo 2014-2015 - Sambache Perugachi, María Fernanda (2016)
Inclusion is that interaction of society without take in account physical cultural and social condition, everything around them with the same conditions, same rights and opportunities that others people perfom into diferent activities that allow the fundamental development of the person such as healthy, education, jobs and society. So the inclusion is a process which will allow us to identify and respond to the differences that students have a through a good participation in the learning culture and community, in this way reducing the exclusion in the education to get changes for everyone to socialize with each other and looking for strategies with a broad vision that ncluding all children, they will participate in the community work regardless of special necessities that they have. It is a process with a lot of participation. The inclusion permit all children and teenagers with or without disability learning together in the different institution educatives, so they have help their learning gand goals but the most important the participation of them.